Manipulating martensite transformation to achieve superior strength-ductility synergy in laser powder bed fusion of nickel-aluminium-bronze alloy via heat treatments - Changjun Han; Yujin Zou; Zhi Dong; Gaoling Hu; Shentao Xu; Yongqiang Yang; Di Wang (Virtual and Physical Prototyping)
The metastable β′ martensite microstructure of nickel-aluminium-bronze (NAB) alloys fabricated by laser powder bed fusion (LPBF) significantly compromises their ductility. This work proposed a viable heat treatment strategy to manipulate the martensite transformation of LPBF-printed NAB alloy with superior strength-ductility synergy. The influence of heat treatment temperature on the microstructure evolution, mechanical properties, and fracture behaviour of the as-built NAB alloy was investigated. The results demonstrated that after heat treatment at 750°C for 4 hs, the ultimate tensile strength of the alloy increased from 670 to 784 MPa, while the elongation improved from 1.2% to 21%. The underlying mechanisms responsible for concurrent improvements in mechanical properties were revealed. The enhanced strength is originated from the superior strain hardening capability induced by the refined lamellar structure and high-density heterogeneous interfaces. Moreover, high-density dislocations and well-dispersed nanoprecipitates contributed additional strengthening effects. The coordinated deformation of the coherent lamellar structure effectively mitigated stress concentration, thereby inhibiting microcrack formation and delaying fracture while maintaining ductility. This study offers a promising strategy for the fabrication of high-performance NAB components through heterogeneous lamellar microstructures and provides theoretical guidance for optimising heat treatment processes and customising multi-scale microstructures.